The Design and Analysis of Self-Cleansing Trash Trap for Capturing Floating Debris at the Drainage System - Sharifudin, Mohamad Aliff Aiman (Universiti Teknologi PETRONAS, 2021)
Industrialization and human error had caused severe water pollution. Initiatives to combat the problems have been done thoroughly such as installing trash trap but it seems like it needs improvement on some parts. For instance, the installation of a fixed position trash trap around the world needs regular maintenance from the local authorities to maintain the efficiency of the trash trap. Thus, it involves manpower and cost to keep it running. This project aim is to develop an effective self-cleansing trash trap which is able to reduce the maintenance cost of existing Gross Pollutant Trap (GPT).